Proton center anti-radiation large volume super-retarding concrete and preparation method thereof
Patent Information
- Application Number
- CN202611227044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对现有质子中心防辐射混凝土中子屏蔽效率低、水化热集中易生裂缝、层间易脱层的不足,本发明提供了一种质子中心防辐射大体积超缓凝混凝土及其制备方法
本发明通过梯度密度分层结构配合梯度硼当量的复合防辐射掺合料,实现质子及次级中子的分级梯度阻滞吸收,有效解决了现有技术中单一密度或两层式结构无法适配不同能级辐射、中子屏蔽效率偏低的问题,在满足高能质子束完全屏蔽要求的同时减少了高密度重骨料的整体用量,兼顾屏蔽效能与材料经济性。
Smart Images

Figure CN122968024A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of radiation-resistant concrete technology, and in particular to a proton-center radiation-resistant large-volume ultra-slow-setting concrete and its preparation method. Background Technology
[0002] As the core carrier of precision tumor radiotherapy, the radiation protection wall of the proton center is the core structure to ensure the safety of diagnosis and treatment and prevent radiation leakage. With the popularization of proton therapy technology, the industry has put forward higher requirements for the shielding efficiency, structural stability and long-term durability of radiation-proof large-volume concrete. The core requirement is to solve the problems of temperature cracks, interlayer delamination, strength attenuation and insufficient impermeability caused by the concentrated release of hydration heat of large-volume concrete, while meeting the full spectrum of proton and secondary neutron shielding.
[0003] Currently, the mainstream existing technical solutions are mainly divided into two categories. The first category is full-section single high-density barite-shielded concrete. Its working principle is that the high density of barite aggregate can effectively block high-energy proton beams. This is achieved by mixing and pouring barite aggregate with ordinary silicate cement cementitious system throughout the entire wall section. This solution was widely used in small and medium-sized proton therapy stations in the early days. Its current advantages are simple preparation process, readily available raw materials, and low initial investment cost. However, this solution has obvious defects: the single-density structure cannot achieve gradient absorption of secondary neutrons, the overall boron equivalent is insufficient, resulting in low neutron shielding efficiency, the large amount of cementitious material required under the full-section high-density aggregate ratio, the concentrated release of hydration heat, which can easily generate penetrating temperature cracks, insufficient impermeability, which can easily lead to radiation leakage risks, and the overall dry density is difficult to meet the shielding requirements of high-dose proton beams.
[0004] The second type is a two-layer ordinary shielded concrete structure. Its working principle involves an inner shielding layer and an outer structural load-bearing layer, which respectively bear the functions of radiation shielding and structural load-bearing. This is achieved by pouring two layers of concrete, with an ordinary cement-based interface agent applied between the layers to ensure adhesion. This is currently the mainstream application scheme for newly built proton centers. Its current advantage is that the mix proportions of each layer can be adjusted according to functional requirements, balancing shielding performance and structural load-bearing capacity. However, this scheme still has many shortcomings: there is no transitional range in density and shielding performance between the two layers; excessive difference in interlayer performance can easily lead to stress concentration and interface delamination; the lack of targeted temperature control measures leads to excessive temperature differences between layers causing cracking; the single boron dosage cannot adapt to different radiation energy levels; the addition of phase change temperature control materials can easily cause structural strength decay; the interface impermeability is insufficient; and the poor compatibility between the expanding agent and the phase change material can easily lead to the propagation of microcracks in the structure.
[0005] Neither of the existing two types of solutions can simultaneously meet the comprehensive requirements of high shielding efficiency, no temperature cracks, interface stability, and long-term durability for radiation shielding walls in proton centers. There is an urgent need to develop a special radiation shielding large-volume concrete technology adapted to high-level proton centers to solve the multiple performance shortcomings of the existing solutions. Summary of the Invention
[0006] To address the shortcomings of existing proton-centered radiation-shielding concrete, such as low neutron shielding efficiency, concentrated hydration heat leading to cracks, and easy delamination between layers, this invention provides a large-volume ultra-retarded proton-centered radiation-shielding concrete and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A large-volume, ultra-slow-setting concrete for proton center radiation protection features a gradient density structure comprising an ultra-high-density shielding layer, a transition layer, and a structural load-bearing layer, arranged sequentially from the radiation source side outwards along the thickness of the concrete wall; the dry density of the ultra-high-density shielding layer is not less than 3.9 t / m³. 3 The dry density of the transition layer is 3.2~3.5 t / m³. 3 The dry density of the structural load-bearing layer is 2.6~2.9 t / m³. 3 The phase change temperature of the microcapsule phase change material in the transition layer is 52~62℃, that in the ultra-high density shielding layer is 48~54℃, and that in the structural bearing layer is 42~48℃. The concrete as a whole adopts a compound system of low-heat cementitious system and composite super-retarding admixture. The initial setting time of each layer of concrete is 20~28h. The initial setting time is tested according to the penetration resistance method of GB / T 50080-2016.
[0008] Furthermore, the ultra-high density shielding layer accounts for 30% to 40% of the total wall thickness, the transition layer accounts for 30% to 35% of the total wall thickness, and the structural bearing layer accounts for 25% to 35% of the total wall thickness.
[0009] Furthermore, the ultra-high density shielding layer adopts a three-stage heavy aggregate gradation of magnetite crushed stone, barite crushed stone, and passivated steel shot; the transition layer adopts an aggregate gradation of magnetite crushed stone, barite crushed stone, and natural river sand; and the structural bearing layer adopts an aggregate gradation of magnetite sand, natural river sand, and limestone crushed stone. The steel shot used in the ultra-high density shielding layer has a particle size of 0.5~4.75mm and an apparent density ≥7.5t / m³. 3 .
[0010] Furthermore, the ultra-high density shielding layer, transition layer and structural bearing layer are all mixed with a composite radiation-shielding admixture composed of borosilicate glass powder and silica fume. The boron equivalent of each layer, based on B2O3 as a percentage of the total mass of concrete, is as follows: ultra-high density shielding layer 0.5%~0.7%, transition layer 0.4%~0.6%, structural bearing layer 0.3%~0.5%.
[0011] Furthermore, the core material of the microcapsule phase change material is a paraffin-based or fatty acid-based material, and the wall material is a melamine-formaldehyde resin or silica that is resistant to temperatures not lower than 65°C and to strong alkalinity with a pH ≥ 13. The amount of microcapsule phase change material in the ultra-high density shielding layer is 2% to 4% of the mass of the corresponding layer cementitious material, the amount of microcapsule phase change material in the transition layer is 4% to 6% of the mass of the corresponding layer cementitious material, and the amount of microcapsule phase change material in the structural bearing layer is 5% to 7% of the mass of the corresponding layer cementitious material.
[0012] Furthermore, the low-heat cementitious system is composed of low-heat silicate cement, Grade I fly ash, and ultrafine mineral powder mixed in a mass ratio of 5:3:2.
[0013] Furthermore, the 28-day compressive strength grade of each layer of concrete shall not be lower than C30, and the impermeability grade shall not be lower than P16.
[0014] Furthermore, the interface between adjacent layers is set as a serrated tenon structure with a 30°~40° bevel angle, the serration height of the tenon is 30~40mm, and the interface is coated with a silane coupling agent modified epoxy resin interface agent, with an interface bonding strength of not less than 2.5MPa.
[0015] Furthermore, the composite super-retarding admixture is composed of polycarboxylate superplasticizer, sodium gluconate, hydroxycitric acid, and tartaric acid mixed in a mass ratio of (5~7):(1.5~2.5):(0.5~1.5):(0.5~1.5); the structural bearing layer is also mixed with lightly calcined magnesium oxide expansion agent, the dosage of which is 6%~10% of the mass of the cementitious material of the structural bearing layer, and the restricted expansion rate of the structural bearing layer is 0.02%~0.03%.
[0016] Furthermore, the following steps are included: S1. Prepare the mixtures for the ultra-high density shielding layer, transition layer, and structural bearing layer respectively. During the preparation of each layer's mixture, add the microcapsule phase change material with the corresponding phase change temperature, the low-heat gelling system, and the composite super retarder additive according to the proportion, and stir evenly for later use. S2. On the pouring surface, pour each layer of the mixture layer by layer from the radiation source side to the outside. The interval between pouring of adjacent layers shall not exceed the initial setting time of the lower layer concrete and shall not be greater than 6 hours. Use one or more of the following measures to control the temperature difference between layers to not exceed 8℃: aggregate pre-cooling, ice water mixing, and interlayer insulation. After the lower layer concrete has initially set, use mechanical grooving to form the corresponding tenon and mortise structure on the joint surface of the adjacent layers. After cleaning the laitance, apply silane coupling agent modified epoxy resin interface agent evenly to the surface of the next layer tenon and mortise structure, and then pour the next layer of mixture. S3. After pouring, keep the concrete moist and keep it warm in accordance with the curing specifications for large volume concrete. The curing period shall not be less than 28 days.
[0017] The present invention has the following beneficial effects: This invention achieves graded gradient retardation absorption of protons and secondary neutrons by using a gradient density layered structure combined with a gradient boron equivalent composite radiation shielding dopant. It effectively solves the problems of existing technologies where single-density or two-layer structures cannot adapt to different energy level radiation and have low neutron shielding efficiency. While meeting the requirements for complete shielding of high-energy proton beams, it reduces the overall amount of high-density heavy aggregate, thus balancing shielding effectiveness and material economy.
[0018] This invention achieves phased slow release and precise temperature control of hydration heat by combining microcapsule phase change materials with gradient phase change temperatures, low-heat cementitious systems, and composite super-retarding admixtures. This effectively solves the problems of concentrated release of hydration heat and excessive temperature stress in large-volume concrete that easily lead to penetrating cracks in existing technologies, avoids the risk of radiation leakage caused by temperature cracks, and ensures the long-term service stability of concrete structures.
[0019] This invention achieves a high-strength interlocking connection between adjacent layers through a sawtooth tenon and mortise structure combined with a silane coupling agent-modified epoxy resin interface agent. This effectively solves the problems of stress concentration and interface delamination and cracking caused by large differences in interlayer performance in the prior art. In addition, the high impermeability of each layer further blocks radiation leakage channels. At the same time, the expansion agent added to the structural load-bearing layer offsets the structural shrinkage stress, further improving the overall structural integrity.
[0020] This solution is adaptable to the radiation protection wall construction needs of proton centers with different installed capacities. The thickness and ratio parameters of each layer can be adjusted according to the actual radiation dose. It can meet the protection requirements without the need for additional metal shielding layers, reducing the overall construction cost and construction difficulty of proton centers. It has good application value in various radiation protection scenarios such as medical proton therapy and particle physics experiments. Attached Figure Description
[0021] Figure 1 This is a flowchart of a method for preparing large-volume ultra-retarded proton-centered radiation-resistant concrete proposed in this invention. Figure 2 The bar charts showing the peak hydration heat and heavy aggregate consumption for each group proposed in this invention are as follows: Figure 3 The core performance multi-dimensional radar chart proposed in this invention; Figure 4 This is a line graph showing the relationship between the microcapsule dosage and 28-day compressive strength proposed in this invention. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] 1. Examples and Comparative Examples Example 1 This embodiment is adapted to a proton center protective wall with an installed capacity of 250MeV. The total thickness of the wall is 1.5m, of which the ultra-high density shielding layer accounts for 35% of the total thickness, i.e., 0.525m, the transition layer accounts for 32% of the total thickness, i.e., 0.48m, and the structural bearing layer accounts for 33% of the total thickness, i.e., 0.495m.
[0024] The construction period is summer. The transition layer uses microencapsulated phase change material with a phase change temperature of 55℃, and the ultra-high density shielding layer uses microencapsulated phase change material with a phase change temperature of 52℃. The light-burned magnesium oxide expanding agent used has a specific surface area of 380 m². 2 / kg, calcination temperature 900℃; after soaking the microcapsules in a pH13 simulated concrete pore solution for 90 days, the phase transition enthalpy retention rate was 92.3%. The mix proportions of each layer are as follows by weight: Ultra-high density shielding layer: The low-heat cementitious system is composed of low-heat silicate cement, Grade I fly ash, and ultrafine mineral powder mixed in a mass ratio of 5:3:2, with a total dosage of 280 parts; 320 parts of magnetite crushed stone with a particle size of 10~20mm and 270 parts of barite crushed stone with a particle size of 5~10mm, with a particle size of 0.5~4.75mm and an apparent density of 7.8t / m³. 3 820 parts of passivated steel grit; the composite radiation-shielding admixture includes 55 parts of borosilicate glass powder and 15 parts of silica fume, with a measured boron equivalent of 0.62% (B2O3) of the total concrete mass. The microencapsulated phase change material (paraffin core, melamine-formaldehyde resin wall material) was used in an amount of 8.4 parts, which is 3% of the mass of the cementitious material; the composite super-retarding admixture was composed of polycarboxylate superplasticizer, sodium gluconate, hydroxycitric acid, and tartaric acid mixed in a mass ratio of 6:2:1:1, with a total amount of 7 parts; and 75 parts of mixing water. 0.08% of the cementitious material mass of Wenlun gum was added as a thickening component. The measured dry density was 3.92 t / m³. 3 Initial setting time: 24h; slump at discharge: 170mm; spread: 420mm; 28d compressive strength: 38.2MPa; impermeability grade: P18; measured porosity: 7.2%.
[0025] Transition layer: 260 parts of low-heat cementitious system; 380 parts of magnetite crushed stone (10-20mm particle size), 320 parts of barite crushed stone (5-10mm particle size), and 180 parts of natural river sand; composite radiation-shielding admixture including 45 parts of borosilicate glass powder and 12 parts of silica fume, with a measured boron equivalent (B2O3) of 0.51% of the total concrete mass; 13 parts of microencapsulated phase change material (55℃ phase change temperature), accounting for 5% of the cementitious material mass; 6.5 parts of composite super-retarding admixture; and 72 parts of mixing water. 0.06% of the cementitious material mass of warm wheel adhesive is added as a thickening component. Measured dry density: 3.35 t / m³. 3 Initial setting time: 23.5h; slump at discharge: 180mm; spread: 440mm; 28d compressive strength: 36.7MPa; impermeability grade: P17; measured porosity: 8.9%.
[0026] Structural load-bearing layer: 240 parts of low-heat cementitious system; 580 parts of limestone crushed stone with a particle size of 10-25mm, 120 parts of magnetite sand, and 320 parts of natural river sand; composite radiation-shielding admixture including 38 parts of borosilicate glass powder and 10 parts of silica fume, with a measured boron equivalent of 0.42% of the total concrete mass (B2O3); 16.8 parts of microencapsulated phase change material (phase change temperature of 44℃), accounting for 7% of the cementitious material mass; and 19.2 parts of lightly calcined magnesium oxide expansion agent, accounting for 8% of the cementitious material mass, with a measured restricted expansion rate of 0.025%. The dosage of the composite super-retarding admixture was 6 parts; the mixing water was 70 parts. The measured dry density was 2.87 t / m³. 3 Initial setting time: 23 hours; 28-day compressive strength: 35.1 MPa; impermeability grade: P16; measured porosity: 12.4%.
[0027] The construction process strictly follows the preparation method steps: When preparing the mixture for each layer of S1, first premix the microcapsule phase change material with an equal mass of cementitious material for 3 minutes, then put it into the mixer and stir at a low speed of 30 r / min for 5 minutes to avoid microcapsule breakage. The thickening component should be mixed evenly with the dry powder of cementitious material in advance. S2 uses three pump trucks to advance the pouring from the radiation source side to the outside in a stepped manner, with a speed of 0.8 m / h and a 5-hour interval between adjacent layers. A comprehensive approach is adopted, including pre-cooling the aggregate to 8°C, mixing with ice water (water temperature 2°C), and covering the layers with insulation cotton, to control the temperature difference between layers to 6°C. After the initial setting of the lower layer of concrete, a 35° beveled mortise and tenon structure is formed using a mechanical grooving process, with a serration height of 35mm. After grooving, the surface laitance and loose particles are cleaned, and the base surface is controlled to be saturated and dry (surface moisture content ≤6%). Then, a 0.8mm thick silane coupling agent modified epoxy resin interface agent is evenly coated, and the measured interface bonding strength is 3.2MPa.
[0028] After the S3 concrete is poured, it is kept moist and heated for 28 days. The temperature difference between the inside and the surface of the concrete is controlled at 22℃, and the temperature difference between the surface and the environment is controlled at 18℃. The cooling rate is 1.5℃ / day. Temperature measurement points are set up according to the requirements of GB 50496-2018 to monitor the changes in the internal temperature field in real time.
[0029] Example 2 This embodiment is adapted to a proton center protective wall with an installed capacity of 230MeV. The total thickness of the wall is 1.8m, of which the ultra-high density shielding layer accounts for 30% of the total thickness, i.e., 0.54m, the transition layer accounts for 35% of the total thickness, i.e., 0.63m, and the structural bearing layer accounts for 35% of the total thickness, i.e., 0.63m.
[0030] Construction will take place in spring and autumn. The transition layer will use microencapsulated phase change material with a phase change temperature of 52℃, and the ultra-high density shielding layer will use microencapsulated phase change material with a phase change temperature of 48℃. The light-burned magnesium oxide expanding agent used has a specific surface area of 380 m². 2 / kg, calcination temperature 900℃. The proportions of each layer by weight are as follows: Ultra-high density shielding layer: 275 parts of low-heat cementitious system (low-heat silicate cement, Class I fly ash, and ultrafine mineral powder in a 5:3:2 ratio); 330 parts of magnetite crushed stone, 265 parts of barite crushed stone, and 810 parts of passivated steel grit (particle size 0.5~4.75mm, apparent density 7.8t / m³). 3 The mixture consisted of: 45 parts borosilicate glass powder, 12 parts silica fume (measured boron equivalent as B2O3 accounting for 0.52% of the total concrete mass); 8.25 parts microencapsulated phase change material (paraffin core, melamine-formaldehyde resin wall material, phase change temperature 48℃), representing 3% of the cementitious material mass; 6.8 parts composite super-retarding admixture (polycarboxylate superplasticizer, sodium gluconate, hydroxycitric acid, tartaric acid in a mass ratio of 6:2:1:1); 74 parts mixing water; and 0.08% warm wheel adhesive added by weight of the cementitious material. The measured dry density was 3.91 t / m³. 3 Initial setting time: 23 hours; 28-day compressive strength: 39.5 MPa; impermeability grade: P18; measured porosity: 7.0%.
[0031] Transition layer: 255 parts of low-heat cementitious system; 390 parts of magnetite crushed stone, 315 parts of barite crushed stone, and 175 parts of natural river sand; 38 parts of borosilicate glass powder and 10 parts of silica fume (measured boron equivalent 0.43%); 12.75 parts of microencapsulated phase change material (52℃ phase change temperature), accounting for 5% of the cementitious material mass; 6.4 parts of composite super-retarding admixture; 71 parts of mixing water; and 0.06% of warm wheel adhesive added by weight of cementitious material. Measured dry density: 3.22 t / m³; initial setting time: 22.5 h; 28-day compressive strength: 37.2 MPa; impermeability grade: P17; measured porosity: 8.5%.
[0032] Structural bearing layer: 235 parts of low-heat cementitious system; 590 parts of limestone crushed stone, 115 parts of magnetite sand, and 315 parts of natural river sand; 32 parts of borosilicate glass powder and 8 parts of silica fume (measured boron equivalent 0.35%); 14.1 parts of microencapsulated phase change material (phase change temperature 42℃), accounting for 6% of the cementitious material mass; 18.8 parts of light-burned magnesium oxide expanding agent, accounting for 8% of the cementitious material mass, with a measured restricted expansion rate of 0.025%; 5.9 parts of composite super-retarding admixture; and 69 parts of mixing water. Measured dry density: 2.62 t / m³ 3 Initial setting time 22h, 28d compressive strength 34.8MPa, impermeability grade P16, measured porosity 13.1%.
[0033] The construction process is the same as in Example 1: S1 Microcapsule premixing followed by low-speed stirring; S2 Three pump trucks for stepped pouring, with a 5-hour interval between adjacent layers, using room temperature mixing (water temperature 20℃), and covering the layers with insulation cotton to control the temperature difference between layers to 7℃; After the lower layer of concrete has initially set, mechanically grooved to form 32° beveled sawtooth tenons with a sawtooth height of 32mm, and coated with 0.8mm silane coupling agent modified epoxy resin interface agent, with an interface bond strength of 3.1MPa; S3 Curing for 28 days.
[0034] Example 3 This embodiment is suitable for a 250MeV high-dose proton center. The total wall thickness is 2m, with an ultra-high-density shielding layer accounting for 40% (0.8m), a transition layer accounting for 30% (0.6m), and a structural load-bearing layer accounting for 30% (0.6m). Construction is carried out during the high-temperature summer season. The transition layer uses microencapsulated phase change material with a phase transition temperature of 62℃, and the ultra-high-density shielding layer uses microencapsulated phase change material with a phase transition temperature of 54℃. The parameters for lightly calcined magnesium oxide are the same as above. Mix proportions for each layer: Ultra-high density shielding layer: 285 parts of low-heat cementitious system; 315 parts of magnetite crushed stone, 275 parts of barite crushed stone, 830 parts of passivated steel grit; 60 parts of borosilicate glass powder, 15 parts of silica fume (measured boron equivalent 0.68%); 11.4 parts of microencapsulated phase change material (54℃), accounting for 4% of the cementitious material mass; 7.2 parts of composite super-retarding admixture; 76 parts of mixing water; 0.08% thermal sizing agent. Measured dry density: 3.95 t / m³ 3 Initial setting time 25h, 28d compressive strength 37.8MPa, impermeability grade P19, porosity 6.8%.
[0035] Transition layer: 265 parts of low-heat cementitious system; 375 parts of magnetite crushed stone, 325 parts of barite crushed stone, and 185 parts of natural river sand; 50 parts of borosilicate glass powder and 13 parts of silica fume (measured boron equivalent 0.56%); 13.25 parts of microencapsulated phase change material (62℃), accounting for 5% of the cementitious material mass; 6.6 parts of composite super-retarder admixture; 73 parts of mixing water; and 0.06% of thermal slurry. Measured dry density: 3.48 t / m³ 3 Initial setting time 24.5h, 28d compressive strength 36.2MPa, impermeability grade P17, porosity 9.2%.
[0036] Structural bearing layer: 245 parts of low-heat cementitious system; 550 parts of limestone crushed stone, 140 parts of magnetite sand, and 330 parts of natural river sand; 40 parts of borosilicate glass powder and 10 parts of silica fume (measured boron equivalent 0.45%); 17.15 parts of microencapsulated phase change material (46℃), accounting for 7% of the cementitious material mass; 19.6 parts of light-burned magnesium oxide expanding agent, accounting for 8% of the cementitious material mass, with a measured restricted expansion rate of 0.028%; 6.1 parts of composite super-retarding admixture; and 71 parts of mixing water. Measured dry density: 2.88 t / m³ 3 Initial setting time: 24 hours; 28-day compressive strength: 35.7 MPa; impermeability grade: P18; porosity: 12.8%.
[0037] Construction process: S1 is the same as before; S2 pouring interval is 5h, interlayer temperature difference is 5℃, tenon and mortise angle is 38°, saw tooth height is 38mm, interface bonding strength is 3.3MPa; S3 curing is 28d.
[0038] Comparative Example 1 This comparative example uses a single high-density barite concrete scheme for the entire cross-section, with a total wall thickness of 1.5m and a dry density of 3.9t / m³. 3 The mix proportions are: 380 parts of P·O 42.5 ordinary Portland cement, no mineral admixtures, 1520 parts of barite aggregate with a particle size of 5-20mm, 20 parts of borax, and 90 parts of water. The measured boron equivalent is 1.0%, the 28-day compressive strength is 32MPa, the impermeability grade is P10, the peak heat of hydration is 68℃, and the heavy aggregate consumption is 72t / 10m³. 3 The wall material cost was 1.35 times that of Example 1, the wall weight was 28% higher than that of Example 1, and three through-temperature cracks with a width of 0.12 mm appeared.
[0039] Comparative Example 2 The same three-layer gradient density structure and proportions (containing borosilicate glass powder, lightly calcined magnesium oxide, and warm-wheel adhesive) as in Example 1 were adopted, except that the phase transition temperature of each microcapsule was uniformly set to 48℃. Therefore, each microcapsule layer used a 48℃ phase transition material, with the dosage corresponding to that in Example 1 (3% for the ultra-high density layer, 5% for the transition layer, and 7% for the structural bearing layer). The construction parameters were the same. Measured data: peak hydration heat 57℃, interlayer temperature difference 12℃, two interfacial microcracks (0.06mm) appeared, impermeability grade P14 / P12 / P12, and interfacial bond strength 2.1MPa. Other properties such as dry density and strength were basically the same as in Example 1.
[0040] Table 1 Comparison of core performance parameters between the examples and comparative examples Note: The boron equivalent gradient is based on B2O3 as a percentage of the total mass of concrete; the relative material cost is 1 for Example 1; Comparative Example 2 retains the same dry density and boron equivalent, as only the phase transition temperature is changed.
[0041] This table compares the core performance parameters of each group. The strength, impermeability, and temperature control indicators of the three embodiments all meet the design requirements. The consumption of heavy aggregate and material cost are much lower than those of Comparative Example 1, the peak heat of hydration is lower than that of the two comparative examples, and no cracks are generated in any of the three embodiments. Comparative Example 1, with its uniform density throughout the wall, has high consumption of heavy aggregate, large heat of hydration, and is prone to cracking. Comparative Example 2, with its single phase change temperature scheme, has poor temperature control and is prone to micro-cracks between layers. This verifies that the present invention can simultaneously solve the three core defects of the prior art.
[0042] 2. Core Performance Verification 2.1 Shielding performance verification The shielding effect of a 250MeV proton beam was simulated using the MCNP program. The three-layer structure in Example 1 has an equivalent lead equivalent of 3.2 mmPb, meeting the design requirement of ≥2.5 mmPb. The secondary neutron transmittance is only 0.02%, and the gamma-ray transmittance is 0.01%. The neutron attenuation coefficient was tested according to ASTM C637 standard, and the ultra-high density shielding layer is 0.82 cm². -1 The transition layer is 0.71cm. -1 The structural load-bearing layer is 0.63cm. -1 The overall neutron attenuation efficiency is 22% higher than that of the control group 1, effectively solving the problem of insufficient shielding efficiency in existing technologies.
[0043] The equivalent lead equivalents of Examples 2 and 3 are 3.0 mm Pb and 3.4 mm Pb, respectively, both of which meet the design requirements. The neutron attenuation efficiencies are 99.92% and 99.99%, respectively, verifying the adaptability of the gradient density structure combined with the gradient boron equivalent design under different installed capacities.
[0044] 2.2 Demonstration of Temperature Control Effectiveness The temperature control mechanism of microencapsulated phase change materials is as follows: when the internal temperature of concrete rises to the phase change point, the core material absorbs 180~200 J / g of latent heat through a solid-liquid phase change, locking the internal temperature near the phase change point and reducing the peak temperature rise. DSC curve data shows: The ultra-high density layer microcapsules used in Example 1 (nominal phase transition temperature 52℃) had an actual phase transition onset temperature of 50.3℃, a peak temperature of 52.1℃, and a phase transition enthalpy of 192 J / g; the transition layer microcapsules (nominal phase transition temperature 55℃) had an actual phase transition onset temperature of 53.5℃, a peak temperature of 55.2℃, and a phase transition enthalpy of 188 J / g; and the structural support layer microcapsules (nominal phase transition temperature 44℃) had an actual phase transition onset temperature of 42.8℃, a peak temperature of 44.1℃, and a phase transition enthalpy of 186 J / g. The measured peak values deviated from the nominal temperatures by ≤±2℃, which conforms to the industry tolerances for phase change materials, and the gradient sequence is completely consistent with the design values.
[0045] Thermal stability test: After thermal aging at 65℃ for 48h, the core material leakage was characterized by the retention rate of phase change enthalpy using DSC. The retention rates of phase change enthalpy for each microcapsule layer were 98.8%, 98.5%, and 98.3%, respectively, corresponding to core material leakage rates of ≤2%, far below the 3% limit. No wall material cracking and no significant core material leakage were observed. The peak hydration heat values for Examples 2 and 3 were 46.5℃ and 47.2℃, respectively, both below the 50℃ threshold, and no temperature cracks were observed, demonstrating the reliability of the gradient phase change temperature control scheme under a wide range of operating conditions.
[0046] 2.3 Mechanical and Durability Verification Tests on the relationship between microcapsule dosage and strength showed that the 28-day compressive strength was 37.5 MPa at 5% of the cementitious material mass, 36.2 MPa at 6%, 35.1 MPa at 7%, 34.8 MPa at 8%, and decreased to 28.5 MPa at 9% (not meeting the C30 requirement). Considering the actual strength dispersion coefficient of approximately 15% in engineering projects, and the strength guarantee rate of less than 95% at an 8% dosage, the upper limit of microcapsule dosage in the structural load-bearing layer was determined to be 7%, balancing temperature control and structural safety margin.
[0047] Compatibility tests between the lightly calcined magnesium oxide expander and the microcapsules showed an expansion rate change of 3.2%, meeting the design requirement of ≤5%. The 60-day shrinkage rates for each layer were as follows: Ultra-high density shielding layer 1.8 × 10⁻⁶ -4 Transition layer 1.6×10 -4 The structural bearing layer is 1.5×10 -4 The difference in interlayer shrinkage rate is 0.3×10. -4 Referring to the "Standard for Construction of Mass Concrete" GB 50496-2018, when the difference in interlayer shrinkage exceeds 2×10⁻⁶... -4At that time, the interfacial shear stress will exceed the bond strength, causing delamination. The measured value of this invention is much lower than the safety threshold and will not cause shrinkage stress cracking.
[0048] The interfacial bond strengths of Examples 2 and 3 were 3.1 MPa and 3.3 MPa, respectively, both ≥2.5 MPa. No microcracks were found at the interface, verifying the effectiveness of the interfacial agent in the tenon and mortise structure.
[0049] 2.4 Verification of raw material parameters The borosilicate glass powder has a chemical composition of 60%~65% SiO2, 20%~25% B2O3, and 10%~18% Na2O. Boron ions are fixed in the glass network structure, with a slow-release period of ≥50 years. The annual boron ion leaching rate was tested according to the ASTM C1303-23 leaching test method. The annual leaching rate of Example 1 was 0.002%, and that of Comparative Example 1 was 0.03% (because ordinary borax is easily leached in an alkaline environment). The leaching rate of the borosilicate glass powder used in this invention is far below the ≤0.01% limit required for long-term proton center shielding stability, ensuring long-term stable shielding performance and avoiding the problem of insufficient boron equivalent in the later stages due to early borax leaching.
[0050] The measured heat of hydration of the low-heat cementitious system at 7 days was 202 kJ / kg, which is ≤210 kJ / kg, far lower than the design limit of 320 kJ / kg for ordinary Portland cement, effectively reducing the total heat of hydration release.
[0051] Table 2 Comparison of Key Performance Indicators Note: Microcapsule leakage rate is calculated based on DSC phase transition enthalpy retention rate (after 65℃ / 48h heat aging).
[0052] This table clearly presents the compatibility of each group of key performance indicators with current specifications and proton center-specific requirements. All indicators in the three examples meet the limit requirements. Comparative Example 1 fails to meet the standards for equivalent lead, neutron attenuation efficiency, peak hydration heat, interfacial bonding strength, impermeability grade, and boron ion release rate, corresponding to the three core defects of existing technologies: insufficient shielding efficiency, easy cracking, and poor long-term stability. Comparative Example 2 also fails to meet the standards for peak hydration heat, interfacial bonding strength, and impermeability grade, verifying the necessity of the gradient phase change temperature control scheme. Overall, the data confirms the reliability of the technical solution of this invention.
[0053] refer to Figure 2 This figure visually illustrates the core differences in temperature control performance and material costs among the various groups. The peak hydration heat of all three embodiments is below the safety limit of 50°C, and the consumption of heavy aggregate is below 60t / 10m³. 3Compared to Comparative Example 1, the peak heat of hydration is reduced by more than 30% and the consumption of heavy aggregate is reduced by 28%, solving the defects of existing single high-density concrete with excessively high heat of hydration leading to cracking and excessive consumption of heavy aggregate resulting in high costs. Compared to Comparative Example 2 with a single phase change temperature, the peak heat of hydration is reduced by about 17%, verifying the temperature control advantages of the gradient phase change temperature control scheme. At the same time, the gradient density structure significantly reduces the amount of heavy aggregate while ensuring shielding performance, combining technical and economic rationality.
[0054] refer to Figure 3 This diagram covers three core assessment dimensions: shielding performance, mechanical performance, and durability performance. It allows for a direct comparison of the performance compliance of each group. All indicators in the three examples fully cover the standard requirements, with no performance shortcomings. Comparative Example 1 only barely meets the compressive strength standard, while the other four indicators are far below the limits, failing to meet the proton center protection requirements. Comparative Example 2 meets the shielding performance standard, but the interface bonding strength and impermeability grade do not meet the requirements, posing a risk of interface cracking and radiation leakage. This verifies that the combination scheme of gradient density + tenon-and-mortise interface + gradient boron content of the present invention can fully meet the multi-dimensional performance requirements of proton center protection concrete, with no technical shortcomings.
[0055] refer to Figure 4 This figure clearly shows the influence of microcapsule dosage on the mechanical properties of concrete. As the microcapsule dosage increases, the 28-day compressive strength of concrete shows a linear decreasing trend. When the dosage does not exceed 7%, the compressive strength is higher than the C30 grade requirement of 30 MPa. When the dosage increases to 9%, the strength drops below the limit. This verifies the rationality of setting the maximum microcapsule dosage to 7% in this invention. While ensuring the gradient phase change temperature control effect, it also reserves sufficient strength safety margin, avoiding the risk of insufficient structural mechanical properties caused by excessive microcapsule dosage. At the same time, it can guide the flexible adjustment of microcapsule dosage under different working conditions to adapt to the project needs of different seasons and different installed capacities.
[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A large-volume, ultra-retarded proton-centric radiation-shielding concrete, characterized in that, A gradient density structure is constructed along the thickness of the concrete wall, from the radiation source side outwards, consisting of an ultra-high density shielding layer, a transition layer, and a structural load-bearing layer; the dry density of the ultra-high density shielding layer is not less than 3.9 t / m³. 3 The dry density of the transition layer is 3.2~3.5 t / m³. 3 The dry density of the structural load-bearing layer is 2.6~2.9 t / m³. 3 ; The phase change temperature of the microcapsule phase change material in the transition layer is 52~62℃, that in the ultra-high density shielding layer is 48~54℃, and that in the structural bearing layer is 42~48℃. The concrete as a whole adopts a compound system of low-heat cementitious system and composite super-retarding admixture. The initial setting time of each layer of concrete is 20~28h, and the initial setting time is tested according to the penetration resistance method of GB / T 50080-2016.
2. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The ultra-high density shielding layer accounts for 30% to 40% of the total wall thickness, the transition layer accounts for 30% to 35% of the total wall thickness, and the structural load-bearing layer accounts for 25% to 35% of the total wall thickness.
3. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The ultra-high density shielding layer uses a three-stage heavy aggregate gradation of magnetite crushed stone, barite crushed stone, and passivated steel shot; the transition layer uses an aggregate gradation of magnetite crushed stone, barite crushed stone, and natural river sand; and the structural bearing layer uses an aggregate gradation of magnetite sand, natural river sand, and limestone crushed stone. The steel shot used in the ultra-high density shielding layer has a particle size of 0.5~4.75mm and an apparent density ≥7.5t / m³. 3 .
4. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The ultra-high density shielding layer, transition layer and structural bearing layer are all mixed with a composite radiation-shielding admixture composed of borosilicate glass powder and silica fume. The boron equivalent of each layer, calculated as B2O3 as a percentage of the total mass of concrete, is as follows: ultra-high density shielding layer 0.5~0.7%, transition layer 0.4~0.6%, structural bearing layer 0.3~0.5%.
5. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The core material of the microcapsule phase change material is a paraffin-based or fatty acid-based material, and the wall material is a melamine-formaldehyde resin or silica that is resistant to temperatures not lower than 65°C and to strong alkalinity with a pH ≥ 13. The amount of microcapsule phase change material in the ultra-high density shielding layer is 2% to 4% of the mass of the corresponding layer cementitious material, the amount of microcapsule phase change material in the transition layer is 4% to 6% of the mass of the corresponding layer cementitious material, and the amount of microcapsule phase change material in the structural bearing layer is 5% to 7% of the mass of the corresponding layer cementitious material.
6. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The low-heat cementitious system is composed of low-heat silicate cement, Grade I fly ash, and ultrafine mineral powder mixed in a mass ratio of 5:3:
2.
7. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The 28-day compressive strength grade of each layer of concrete shall not be lower than C30, and the impermeability grade shall not be lower than P16.
8. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The interface between adjacent layers is set as a serrated tenon and mortise structure with a 30°~40° bevel angle. The serration height of the tenon and mortise is 30~40mm. The interface is coated with a silane coupling agent modified epoxy resin interface agent, and the interface bonding strength is not less than 2.5MPa.
9. The proton-center radiation-shielding large-volume ultra-retarded setting concrete according to claim 1, characterized in that, The composite super-retarding admixture is composed of polycarboxylate superplasticizer, sodium gluconate, hydroxycitric acid, and tartaric acid in a mass ratio of (5~7):(1.5~2.5):(0.5~1.5):(0.5~1.5); the structural bearing layer is also mixed with lightly calcined magnesium oxide expansion agent, the dosage of which is 6%~10% of the mass of the cementitious material of the structural bearing layer, and the restricted expansion rate of the structural bearing layer is 0.02%~0.03%.
10. A method for preparing large-volume ultra-retarded proton-center radiation-shielding concrete, used to prepare the large-volume ultra-retarded proton-center radiation-shielding concrete as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S1. Prepare the mixtures for the ultra-high density shielding layer, transition layer, and structural bearing layer respectively. During the preparation of each layer's mixture, add the microcapsule phase change material with the corresponding phase change temperature, the low-heat gelling system, and the composite super retarder additive according to the proportion, and stir for later use. S2. On the pouring surface, pour each layer of the mixture layer by layer from the radiation source side outwards. The interval between adjacent pouring layers shall not exceed the initial setting time of the lower layer concrete and shall not be greater than 6 hours. Use one or more of the following measures to control the temperature difference between layers to not exceed 8℃: aggregate pre-cooling, ice water mixing, and interlayer insulation. After the lower layer concrete has initially set, use mechanical grooving to form the corresponding tenon and mortise structure on the joint surface of the adjacent layers. After cleaning the laitance, apply silane coupling agent modified epoxy resin interface agent to the surface of the next layer tenon and mortise structure, and then pour the next layer of the mixture layer. S3. After pouring, keep the concrete moist and keep it warm in accordance with the curing specifications for large volume concrete. The curing period shall not be less than 28 days.